Modification of Culvert Design on Discharge Channel: A Case Study in Indonesian Coal-Fired Power Plant - Dwi Rian Sulaeman; Zakie Anugia; Muhammad Idris; Istiarto Istiarto; Sigit Nurhady (Journal of Engineering and Technological Sciences, 2023)
The construction of a new CFPP in Indonesia, which was located next to three existing power plants and utilized an existing discharge channel, faced the problem of insufficient capacity of the existing discharge channel to deliver water to four power plants. The problem occurred not only because of the overcapacity of the cooling water flow proposed by the new CFPP but also because of the small size of the culvert located in the discharge channel. This paper discusses several methods to overcome this problem by enlarging the culvert area or by removing the culvert from the channel and replacing it with a bridge. A hydraulic study was investigated using the HEC-RAS software by utilizing inputs obtained from the existing channel geometry and flow measurement data. It was found that additional culverts on both sides with a size of 2 m x 4 m and 3 m x 1 m could reduce the water level by 1.12 m and 0.39 m, respectively. Meanwhile, removing the culvert provided a significant water level reduction of 1.39 m. Enlarging the culvert was chosen as the solution to the discharge channel capacity issue since removing the culvert would require temporarily closing the channel during construction and stopping the operation of the existing power plant.